Projeto KABEN DJUOI de manejo florestal dos Xicrin do Catete: perspectivas econômicas históricas e político-institucionais - INDRIUNAS, Luís Cláudio (Universidade Federal do Pará, 2011)
This work is a study case of the sustainable timber project Kaben Djuoi form indigenous Xikrin do Cateté, located in Southern Pará. The research was based on historical, economical, political and cultural perspectives. One of the aims was identifying social actors who have political or technical involvement with Xikrins reality and, more specifically, are involved in the projects context. Survey, documental and bibliographical research were the bases of the work, wich tries to check the facts through theoretical and practical concepts of sustainable development. Historical and cultural aspects of this ethnical group were described in detail, as well as, geographical and environmental context of the region. About the results, the research tries to show the limitation of the studied project, which has been stopped before the surveys. Details about political behavior of the Xikrin with other institutions, specially the CVRD company and the non-governmental organization ISA, were also described.